An Integrated Analysis of Rural Renewal PlansUsing DPSIR Method in Iran - Mohsen Sartipi Pour; Sahar Nedaii Tousi; Sima Sa’adat Shourak Haji (صفه)
Due to its multi-functional life-subsistence nature, the assessment and planning of rural housing is a complex issue. The varying tendencies of villagers from their housing over time, as well as non-participatory, positivist, top-down approaches of housing development programmes have exacerbated complexities and reduced efficiency, leading to inconsistencies between implementation and objectives, in terms ofboth process and content. Assessment is, therefore, a systematic pathological method, and can be used as an effective tool for improving and updating programmes. Accordingly, the agenda here is paying attention to the integrated analysis and rooting out the causes of possible content and process inconsistencies within the “Rural Improvement and Renewal plan”. Within the framework of evaluative research methodthrough a selected assessment model, and using random survey and targeted categorisation, 31provinces of the country were evaluated, using 4334 residential files, consisting of multiple criteria and indicators.The results show that despite the relative success of the Rural Improvement and Renewal Plan, the most important reasons for the inconsistency between design and implementation are the reluctance of design offices to design and promote appropriate, innovative, up-to-date and need-based models, a shortage of attention to livelihood-based housing and subsistence-related needs in design.One can also mention the inefficiency and incorrect implementation mechanisms for allocating quotas and recognising the eligibility of applicants, the damages in design, implementation, and supervision stages and the inadequacy of local work forces with increasing the workloadscaused by the plan.Other issues are holding duplicate, irrelevanttraining courses in some areas,and inefficient implementation of empowerment plans by local authorities as well as financial debts and arrears. To conclude, a set of strategic principles are proposed to improve and enhance the mechanisms of special plans.